Extracts of Perilla frutescens var. Acuta (Odash.) Kudo Leaves Have Antitumor Effects on Breast Cancer Cells by Suppressing YAP Activity. (15th February 2021) - Kim, Cho-Long; Shin, Yu-Su; Choi, Sue-Hee; Oh, Seroc; Kim, Kyeongseob; Jeong, Han-Sol; Mo, Jung-Soon
Abstract : Yes-associated protein (YAP)/WW domain-containing transcription factor (TAZ) is critical for cell proliferation, survival, and self-renewal. It has been shown to play a crucial oncogenic role in many different types of tumors. In this study, we investigated the antitumor effect of the extracts of Perilla frutescens var. acuta (Odash.) Kudo leaves (PLE) on Hippo-YAP/TAZ signaling. PLE induced the phosphorylation of YAP/TAZ, thereby inhibiting their activity. In addition, the treatment suppresses YAP/TAZ transcriptional activity via the dissociation of the YAP/TAZ-TEAD complex. To elucidate the molecular mechanism of PLE in the regulation of YAP activity, we treated WT and cell lines with gene knockout (KO) for Hippo pathway components with PLE. The inhibitory effects of PLE on YAP-TEAD target genes were significantly attenuated in LATS1/2 KO cells. Moreover, we found the antitumor effect of PLE on MDA-MB-231 and BT549, both of which are triple-negative breast cancer (TNBC) cell lines. PLE reduced the viability of TNBC cells in a dose-dependent manner and induced cell apoptosis. Further, PLE inhibited the migration ability in MDA-MB-231 cells. This ability was weakened in YAP and TEAD-activated clones suggesting that the inhibition of migration by PLE is mainly achieved by regulating YAP activity. Taken together, the results of this study indicate that PLE suppressed cell growth and increased the apoptosis of breast cancer (BC) cells via inactivation of YAP activity in a LATS1/2-dependent manner.